If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5h + -7 = 3h + -15 Reorder the terms: -7 + 5h = 3h + -15 Reorder the terms: -7 + 5h = -15 + 3h Solving -7 + 5h = -15 + 3h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-3h' to each side of the equation. -7 + 5h + -3h = -15 + 3h + -3h Combine like terms: 5h + -3h = 2h -7 + 2h = -15 + 3h + -3h Combine like terms: 3h + -3h = 0 -7 + 2h = -15 + 0 -7 + 2h = -15 Add '7' to each side of the equation. -7 + 7 + 2h = -15 + 7 Combine like terms: -7 + 7 = 0 0 + 2h = -15 + 7 2h = -15 + 7 Combine like terms: -15 + 7 = -8 2h = -8 Divide each side by '2'. h = -4 Simplifying h = -4
| 6(b-2)+24=42 | | 4r+4=9r+14 | | 7p-5=4p+4 | | -2+26=6 | | 12+4=x | | -18+24x+2x=8x+88 | | x.x=x/12345678910.(x+13) | | x.x=x/12345678910 | | 6xy+6y^2+10x^2-x-2y=0 | | 14x^2-32x+18=0 | | x.x=x-12345678910 | | 27-3x=6-10x | | x=x-12345678910 | | x^2+y^2+4x-8y+15=0 | | x-x.x=x-123892749194719470000000000000000000000000000 | | x-x.x=x-12389274919471947 | | x-x.x=x-12 | | 7+5x=15+x | | 24+2y=-6y | | 28-21x=16x-18+6 | | x*lnx=2*lnx | | -6(2t+1)=-54 | | f(x)=-2Sq+2x+2 | | 4(f-10)=-52 | | 14-6x=6-7x | | 4x+6=-57-5x | | 10(s-5)=-95 | | 19232=10a+108b | | 4+12x=-62+x | | (2x-5)+x=(8x+20)+32 | | y^6-3y^3-2=0 | | 4(x-1)=3x+2 |